Physiological and energetic demands during still-rings routines of elite artistic gymnasts - Seemann-Sinn, A.; Rüdrich, P.; Gorges, T.; Naundorf, F.; Wolfarth, B. (International Journal of Sports Physiology and Performance, 2023)
Purpose: The aim of the study was to analyze physiological and energetic demands of elite gymnasts during still-rings routines (SRRs).